2015
DOI: 10.1007/s10792-015-0151-x
|View full text |Cite
|
Sign up to set email alerts
|

Safety of undiluted intracameral moxifloxacin without postoperative topical antibiotics in cataract surgery

Abstract: The objective of this study is to evaluate the safety of undiluted 0.5 % intracameral moxifloxacin for postoperative endophthalmitis prophylaxis in cataract surgery patients without the use of additional postoperative topical antibiotics. All phacoemulsification cataract surgeries performed by a single surgeon (B.A.) at the John A. Moran Eye Center from June 2012 to May 2015 were reviewed retrospectively. From June 2012 to April 2014, patients were given topical 0.5 % moxifloxacin postoperatively. From May 201… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…To date there have been no reports in the literature of ocular adverse effects on the iris epithelium following topical use of moxifloxacin. Moreover, toxicity studies have demonstrated a good safety profile of topical and intracameral use of moxifloxacin [14][15][16]. In addition, despite the high concentration of moxifloxacin following intravitreal administration, the rapid clearance of the drug within the first 12 h accounts for the lackof adverse reactions [17].…”
Section: Discussionmentioning
confidence: 99%
“…To date there have been no reports in the literature of ocular adverse effects on the iris epithelium following topical use of moxifloxacin. Moreover, toxicity studies have demonstrated a good safety profile of topical and intracameral use of moxifloxacin [14][15][16]. In addition, despite the high concentration of moxifloxacin following intravitreal administration, the rapid clearance of the drug within the first 12 h accounts for the lackof adverse reactions [17].…”
Section: Discussionmentioning
confidence: 99%
“…Second, there have now been 3 papers 24 from the United States showing that use of intracameral moxifloxacin without postoperative topical antibiotics does not result in a higher endophthalmitis rate. There have been several more papers from around the world demonstrating the same point (that postoperative topical antibiotics are unnecessary in routine, uncomplicated cataract surgery) with intracameral cefuroxime.…”
Section: To the Editormentioning
confidence: 99%
“…It will be interesting to watch if a routine use of intracameral antibiotic would reduce or eliminate routine use of postoperative topical antibiotic. [ 10 ] This will be very beneficial to people living in the developing countries where the cost and compliance are critical issues. In this issue, the rationale and the current evidences of antibiotic prophylaxis in cataract surgery are reviewed.…”
Section: Why Moxifloxacin?mentioning
confidence: 99%